2009
DOI: 10.1371/journal.pone.0007689
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profile of MicroRNAs in Young Stroke Patients

Abstract: BackgroundThe methods currently available for diagnosis and prognosis of cerebral ischaemia still require further improvements. Micro-RNAs (small non-coding RNAs) have been recently reported as useful biomarkers in diseases such as cancer and diabetes. We therefore carried out microRNA (miRNA) profiling from peripheral blood to detect and identify characteristic patterns in ischaemic stroke.Methods/Principal FindingsThe ischaemic stroke patients aged between 18–49 years, characterized based on World Health Org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
318
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(334 citation statements)
references
References 31 publications
11
318
1
4
Order By: Relevance
“…Previous studies have shown that stroke also induces changes in the miRNA expression profiles in rodents, as well as humans (30,31) (Table I).…”
Section: Strokementioning
confidence: 91%
“…Previous studies have shown that stroke also induces changes in the miRNA expression profiles in rodents, as well as humans (30,31) (Table I).…”
Section: Strokementioning
confidence: 91%
“…The technology to measure RNA is evolving, as is the understanding of the many types of RNA that exist. Indeed, most studies to date have focused on messenger RNA, whereas more recently described RNA, such as microRNA and snoRNA, still require further evaluation as potential biomarkers in stroke [30].…”
Section: Biomarkers For the Diagnosis Of Ischemic Strokementioning
confidence: 99%
“…There are several microRNAs that are altered in response to brain injury after stroke or seizures (Liu et al, 2010). In one study of young stroke patients, these profiles correlated with the type of stroke they suffered and the progress of recovery (Tan et al, 2009). These studies demonstrate that microRNAs, if specific and readily detectable at the appropriate times, could be powerful tools not only for the diagnosis, but also the treatment of neurological disorders.…”
Section: Future Research Directionsmentioning
confidence: 99%